Design and experiment on scion cutting mechanism of grafting robot for cucurbit - Chen, Liping; Jiang, Kai; Zhang, Qian; Guo, Wenzhong; Zheng, Wengang (International Journal of Agricultural and Biological Engineering, 2020)
The scion cutting mechanism of the traditional grafting machine cannot correct the bending degree of the scion seedling stem so that the cutting angle of the scion seedling is not standard and the survival rate of the grafted seedling is affected. In this study, cucumber seedlings and watermelon seedlings were taken as experimental objects. Based on the analysis of the geometric parameters and mechanical characteristics of scion seedlings, a scion cutting mechanism with holding seedling applied to cucumber seedlings and watermelon was designed and developed. The main structure and operating parameters of V-shaped holding seedling block and cutting unit were determined, and holding seedling and cutting performance tests were carried out. The test results showed that compared with the common arc clamp, the V-shaped holding seedling block had a better guiding and centering effect on the scion seedling, could better correct the bending state of the scion seedling stem, and the success rate of holding seedling of the V-shaped holding block reached 98.33%, which was increased by 13.33% compared with the arc-shaped clamp, and the seedling injury rate was only 1.67%. The upper and lower two-point positioning of scion stem by clamping hand and holding seedling block can improve the cutting performance effectively. The cutting accuracy rate of the scion was 97.75%, and the cutting success rate was 98.67%. The cutting performance was closely related to the holding seedling effect. The research results can provide a reference for the design of cutting mechanisms of melon grafting robots. Keywords: grafting robot, cutting mechanism, holding seedling block, scion seedlings, cucurbit DOI: 10.25165/j.ijabe.20201305.5810 Citation: Chen L P, Jiang K, Zhang Q, Guo W Z, Zheng W G. Design and experiment on scion cutting mechanism of grafting robot for cucurbit. Int J Agric & Biol Eng, 2020; 13(5): 99–106.